Specific muscle synergies in national elite female ice hockey players in response to unexpected external perturbation - Kim, M.; Kim, Y.; Kim, H.; Yoon, B. (Journal of Sports Sciences, 2018)
This study aimed to investigate specific muscle synergies in elite ice hockey players indicating highly developed postural control strategies used to restore balance against unexpected external perturbations. Seven elite athletes (EA) on the women`s national ice hockey team and 7 non-athletes (NA) participated in this study. Based on trajectories of centre of mass (COM), analysis periods were divided into an initial phase (a balance disturbance after perturbation onset) and a reversal phase (a balance recovery response), respectively. Muscle synergies were extracted at each phase by using non-negative matrix factorization. k-means cluster analysis was performed to arrange similar muscle synergies in all participants. EA showed significantly shorter recovery period of COM and smaller body sway than NA. In the initial phase, we identified 2 EA-specific synergies related to ankle plantar flexors or neck extensors. In the case of an NA-specific synergy, co-activation of the ankle plantar flexors and dorsiflexors was found. In the reversal phase, no specific muscle synergies were identified. As the results, EA-specific muscle synergies showed low co-activation strategy of agonists and antagonists in ankle and neck extensors. Our results could provide critical information for rehabilitation strategies in athletes requiring high postural stability.